1981
DOI: 10.1111/j.1365-2257.1981.tb01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrocytosis in alcohol-related liver disease: its value for screening

Abstract: Summary The incidence of macrocytosis, defined as a mean corpuscular volume (MCV) of > 95 fl and large red cells on peripheral blood film, was determined in 303 alcoholics with liver disease (95 females: 208 males), 60 non‐alcoholics with chronic liver disease (44 females: 16 males) and 35 control subjects (15 females: 20 males). Macrocytosis was found in 70.3% (213/303) of alcoholics with liver disease and in 23.3% (14/60) of non‐alcoholics with liver disease, P < 0.001. MCV values > 100 fl were seen in 49.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Macrocytosis is common in both anemic and nonanemic alcoholics; it appears to be even more common in those without anemia [31]. It has been previously reported that incidence of macrocytosis in female alcoholics was 86% compared to 63% in males [33]. This is in agreement with our study, where almost every second patient had MCV levels above the normal upper borderline.…”
Section: Discussionsupporting
confidence: 94%
“…Macrocytosis is common in both anemic and nonanemic alcoholics; it appears to be even more common in those without anemia [31]. It has been previously reported that incidence of macrocytosis in female alcoholics was 86% compared to 63% in males [33]. This is in agreement with our study, where almost every second patient had MCV levels above the normal upper borderline.…”
Section: Discussionsupporting
confidence: 94%
“…In a study of red blood cell status in alcoholic and nonalcoholic liver disease [32], macrocytic anemia was mostly found in patients with cirrhosis, but in ALD the MCV correlated with the estimated alcohol consumption and decreased after abstinence from alcohol. MCV values > 100 fl in patients with liver disease almost invariably indicated alcohol-related disease [33]. In our study the difference in MCV between ASH and NASH patients seems to be even more marked in fibrosis stages 3 and 4 than in stages 0-2 (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…59 It then takes several months of abstinence for MCV to return to normal, 60 so MCV has no role in monitoring abstinence or relapse. The actual mechanism by which alcohol causes an increase in MCV appears to include a direct toxic effect of alcohol on red blood cells, folic acid de®ciency secondary to alcohol abuse and hepatic damage.…”
mentioning
confidence: 99%